Genetically Encoded and Biologically Produced All‐DNA Nanomedicine Based on One‐Pot Assembly of DNA Dendrimers for Targeted Gene Regulation. Issue 10 (19th January 2021) - Lu, Jingxiong; Hu, Pengchao; Cao, Lingyan; Wei, Zixiang; Xiao, Fan; Chen, Zhe; Li, Yan; Tian, Leilei
Abstract: All‐DNA nanomedicines have emerged as potential anti‐tumor drugs. DNA nanotechnology provides all‐DNA nanomedicines with unlimited possibilities in controlling the diversification of size, shape, and loads of the therapeutic motifs. As DNA is a biological polymer, it is possible to genetically encode and produce the all‐DNA nanomedicines in living bacteria. Herein, DNA‐dendrimer‐based nanomedicines are designed to adapt to the biological production, which is constructed by the flexible 3‐arm building blocks to enable a highly efficient one‐pot DNA assembly. For the first time, a DNA nanomedicine, D4‐3‐As‐DzSur, is successfully genetically encoded, biotechnologically produced, and directly self‐assembled. The performance of the biologically produced D4‐3‐As‐DzSur in targeted gene regulation has been confirmed by in vitro and in vivo studies. The biological production capability will fulfill the low‐cost and large‐scale production of all‐DNA nanomedicines and promote clinical applications. Abstract : A genetically encoded all‐DNA nanomedicine with targeted gene regulation property was produced from E. coli after a range of bioprocessing. This study provides a new approach for production of DNA nanomedicines, which will greatly promote their clinical applications in the future.